ANALISIS PENDEKATAN INTERTEKSTUALITAS TERHADAP AJARAN PERCERAIAN DALAM ALQUR’AN DAN AL-KITAB - Soleh Anwar Pohan; Norain; Laila Sari Masyhur (Almustofa Journal of Islamic Studies and Research, 2025)
In Islam, divorce is seen as the last resort in a family's journey, when all other options have been exhausted, not as a forbidden practice. Article 38 letter b of Law Number 1 of 1974 concerning Marriage contains legal provisions regarding divorce. According to the law, a marriage can be dissolved due to a court decision, divorce, or death. From this it is clear that divorce is a way to end a marriage that is different from other ways (Kamal, 1974). One way of looking at divorce is as the dissolution of a marriage and the end of a marital relationship. According to a number of these definitions, divorce is defined as the termination of the marriage bond between a husband and a wife, which aims to create a stable, eternal, and everlasting household. As a result, the couple is no longer allowed to live together as they should as husband and wife.